Lost and Found In JumpStart Town - Holub, Joan frey50; Sur, Duendes Del. (New York : Scholastic, 2000)
The JumpStart gang goes into town together but each of the 4 gets lost as they visit stores and neighborhoods.
At head of title: JumpStart pre-K.
Keywords: Readers (Primary); Lost children; Friendship